MENUMBUHKAN MINAT KEWIRAUSAHAAN PADA MASA PANDEMI COVID - 19 MELALUI STUDI KELAYAKAN BISNIS - Helena Ni Gusti Ayu Putu Pusparini; I Nyoman Henry Arie Suarthana (STIE Atma Bhakti, 2022)
This review plans to cultivate understudy business venture interest during the Coronavirus pandemic through a business attainability study joined with issue based learning. The number of inhabitants in this review were all understudies of the Administration S1 concentrate on program at Triatma Mulya University. The example utilized in this review was chosen utilizing a purposive examining technique, utilizing the models of understudies who have gotten a business attainability concentrate on course. The consequences of the review show that in acknowledging understudy interest in becoming business visionaries, it very well may be done in the educating and learning process with learning techniques that underline business achievability considers, albeit this exploration is restricted to Blossom's intellectual area, the emotional space and psychomotor space play a significant part in molding interest in turning into a business person. The after effects of the meeting show that understudies are keen on becoming business visionaries as well as they have run it, both as ambitious innovators and business visionaries through a business attainability concentrate on that was dissected beforehand, and this review understudies' advantage in business through a business possibility study to turn into a pioneering understudy was effectively made.